Uniaxial Tension of Yellow Meranti Timber at an Angle to the Grain - Yosafat Aji Pranata; Roky Surono (Wood Research Journal, 2013)
Tensile strength measures the force applied to a timber element/structural element to the point where it breaks. In this paper, a finite element analysis (FEA) of uniaxial tension of Yellow Meranti timber (Shorea spp.), using von Mises Criterion to include orthotropic nature of the material, was used to derive a prediction of tensile strength at an angle to the grain (cross grain) in plane stress (2D) modeling. To investigate the validity of the finite element analysis results, various 5°, 10°, and 15° cross grain specimens of Yellow Meranti (Shorea spp.) were tested in laboratory under uniaxial tension stress using UTM instrument. Comparison with experimental results shows that the FEA simulation predicts the stress-strain curves lower than experimental results, which result shows good agreement, it is seen from %-relative difference which is less than 30%. Calculations were performed with the numerical analysis (FEA) and Experimental Tests gives results that the difference is not too significant, for specimens with a grain angle of 5° difference in outcomes by 27%, for a grain angle of 10° difference in outcomes by 25%, and for a grain angle 15° difference in outcomes by 22%.